Sintesis Senyawa N-fenetil 4-O-asetil ferulamida dari Asam Ferulat melalui Reaksi Amidasi Tidak Langsung - Islam, Muhammad Fajar; Firdaus, Firdaus; Soekamto, Nunuk H. (Indonesian Journal of Chemical Research, 2016)
Compound N-phenetyl 4-O-asetil ferulamide had been synthesized from ferulic acid and phenetylamine through esterification and indirect amidation method. Esterification reaction of ferulic acid with anhydride acetate was done in pyridine solvent at room temperature. Indirect amidation was perform by chlorination using tionyl chloride in benzene solvent at 70Â°C and continued by amidation with phenetylamine, catalyzed by pyridine in dichloromethane solvent at room temperature. the compound obtained is brown yellowish crystal with melting point 118-120Â°C. The rendemen of target compound is 53.81%.